Pharmacokinetics and Pharmacodynamics of Remimazolam (CNS 7056) after Continuous Infusion in Healthy Male Volunteers: Part I. Pharmacokinetics and Clinical Pharmacodynamics - Schüttler, Jürgen; Eisenried, Andreas; Lerch, Marco; Fechner, Jörg; Jeleazcov, Christian; Ihmsen, Harald (Anesthesiology, 2020)
BACKGROUND: Remimazolam (CNS 7056) is a new ultra-short-acting benzodiazepine for intravenous sedation and anesthesia. Its pharmacokinetics and pharmacodynamics have been reported for bolus administration. This study aimed to investigate the pharmacokinetics and pharmacodynamics of remimazolam after continuous infusion. METHODS: Twenty healthy male volunteers (20 to 38 yr, 64 to 99 kg) received remimazolam as continuous intravenous infusion of 5 mg/min for 5 min, 3 mg/min for the next 15 min, and 1 mg/min for further 15 min. Pharmacokinetics of remimazolam and its metabolite were determined from arterial plasma concentrations. Sedation was assessed using the Modified Observer's Assessment of Alertness and Sedation scale. Pharmacokinetic-pharmacodynamic modeling was performed by population analysis. Hemodynamics and the electrocardiogram were also investigated. RESULTS: Pharmacokinetics was best described by a three-compartment model for remimazolam and a two-compartment model with transit compartment for the metabolite. Remimazolam showed a high clearance (1.15 ± 0.12 l/min, mean ± SD), a small steady-state volume of distribution (35.4 ± 4.2 l) and a short terminal half-life (70 ± 10 min). The simulated context-sensitive halftime after an infusion of 4 h was 6.8 ± 2.4 min. Loss of consciousness was observed 5 ± 1 min after start, and full alertness was regained 19 ± 7 min after stop of infusion. Pharmacodynamics of Modified Observer's Assessment of Alertness and Sedation score was best described by a sigmoid probability model with effect site compartment. The half-maximum effect site concentration for a Modified Observer's Assessment of Alertness and Sedation score less than or equal to 1 was 695 ± 239 ng/ml. The equilibration half-time between central and effect compartment was 2.7 ± 0.6 min. Mean arterial blood pressure decreased by 24 ± 6%, and heart rate increased by 28 ± 15%. Spontaneous breathing was maintained throughout the study. There was no significant prolongation of the QT interval of the electrocardiogram observed. CONCLUSIONS: Remimazolam was characterized by a pharmacokinetic-pharmacodynamic profile with fast onset, fast recovery, and moderate hemodynamic side effects.
CRIS-Team Scopus Importer:2020-03-27